Climate impact on consumption and the Water Rationing for rice crop in Babil Governorate (Journal of the College of Education for Women, 2025)
This study addressed the impact of climate, which included the elements (actual solar brightness, temperature, relative humidity, and wind speed) In water consumption and water Codified of eggplant crop in Babylon Governorate, and reliance was placed on the climatic data of the study area station, Al-Hillah station and my control stations are Baghdad and Karbala for a period of 30 years, and I use the (CROPWAT 8.0) program to calculate evapotranspiration using the Penman-Monteith equation developed by the Food and Agriculture Organization (F.A.O) ,The study showed that the month of May was one of the lowest months in terms of the rice crop’s requirement of consumption and water consumption due to the decrease in both temperatures and solar brightness compared to the rest of the growing season, while the rice crop required the largest amount. For consumption and water consumption in the month of July, while the study showed that the amount of consumption and water consumption decreases in September at the end of the growing season due to the full growth of the crop, which requires a small amount of water. Karbala station recorded the lowest amount for water consumption and this is because the end of the growing season is shorter in Karbala compared to other stations.